Positive and negative aspects of participation in illicit drug research: Implications for recruitment and ethical conduct - Barratt, Monica; Norman, J.; Fry, C. (Elsevier BV, 2007)
Improved understanding of incentives and barriers to drug user research participation may improve study recruitment, retention and outcomes and enhance the ethical acceptability of illicit drug research. In Melbourne, Australia during 2001-2004, 507 injecting drug users were recruited from Needle and Syringe Programs and asked to nominate the 'best' and 'worst' things about research. Commonly reported positive aspects of drug research were its capacity to provide valid information about drug use (39%), the potential to improve drug-related policies and practices (20%) and benefits to the community (14%). Reported negative aspects of drug research included concerns about lack of, or negative impact of research findings (31%), and personal dislikes about research projects, such as discomfort (27%), inconvenience (21%) and risk (9%). IDU may participate in non-intervention research because of expected benefits for themselves and others, and may be discouraged from involvement by personal discomfort, inconvenience and risk, or a perceived lack of impact or benefit. To enhance recruitment to non-intervention research and fulfil ethical obligations investigators should (1) actively consider how best to minimise the IDU-defined negative aspects of research, and (2) clarify for prospective participants the intended impact of the research on policy and practice.